Adolescent cognition thinking in a new key - Elkind, David, 1931-; Davidson, Frances W.; Davidson, John M.; Davidson Films (San Luis Obispo, CA : Davidson Films, 1999)
During adolescence, young minds begin working in fresh ways that permit new ways of reasoning that enable students to take on much more challenging materials. However, these transitions can result in inconsistent forms of thinking that create social and emotional difficulties. Referring to the work of Piaget, Erikson, Goffman and his own studies, David Elkind looks at the intellectual, emotional and social changes of this stage of life
Title from title screen
Camera, Gregory Monroe, John Davidson, Emily Davidson ; editors, Kim Baker, John Davidson
Narrated by: David Elkind
Keywords: Self-perception in adolescence; Thought and thinking; Adolescent psychology